2023
DOI: 10.3201/eid2904.221622
|View full text |Cite
|
Sign up to set email alerts
|

Serial Interval and Incubation Period Estimates of Monkeypox Virus Infection in 12 Jurisdictions, United States, May–August 2022

Abstract: Using data from 12 US health departments, we estimated mean serial interval for monkeypox virus infection to be 8.5 (95% credible interval 7.3-9.9) days for symptom onset, based on 57 case pairs. Mean estimated incubation period was 5.6 (95% credible interval 4.3-7.8) days for symptom onset, based on 35 case pairs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…When we applied a longer serial interval distribution with a mean = 8.5 days and a SD = 5.0 days, 17 we estimated a similar pattern of transmission dynamics with R e = 2.29 [95% HPD: 1.58−3.19] and k = 9.63 [95% HPD: 2.74−142.72] (Supporting Information S1: Figure ).…”
Section: Resultsmentioning
confidence: 80%
“…When we applied a longer serial interval distribution with a mean = 8.5 days and a SD = 5.0 days, 17 we estimated a similar pattern of transmission dynamics with R e = 2.29 [95% HPD: 1.58−3.19] and k = 9.63 [95% HPD: 2.74−142.72] (Supporting Information S1: Figure ).…”
Section: Resultsmentioning
confidence: 80%
“…It is not subject to copyright under 17 USC 105 and is also made available (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. In October, we updated estimates of the serial interval for rash onset of 7.0 days (95% CrI 5.8 -8.4) from 40 case pairs and incubation period for rash onset of 7.5 days (95% CrI 6.0 -9.8) from 35 U.S. case-patients and used those as model inputs for EpiNow2 (Madewell et al, 2023). These data were obtained through the collaboration of several U.S. jurisdictions on a special study.…”
Section: W I T H D R a W Nmentioning
confidence: 99%
“…The three-week monitoring period is based on the estimated incubation period 24,25 , in which more than 98% of cases show symptoms within 21 days of exposure. Although the exact duration of the infectious period is unclear, several studies have investigated serial intervals (i.e., the time interval between symptom onset dates of primary and secondary cases) and have suggested that, for symptomatic cases, more than 90% of transmission occurs within two weeks of symptom onset 26,27 . Recent findings have also indicated that there might be considerable heterogeneity in the infectious period between infected individuals.…”
Section: Main Textmentioning
confidence: 99%